Familial writer’s cramp: a clinical clue for inherited coenzyme Q10 deficiency - Amprosi, Matthias; Zech, Michael; Steiger, Ruth; Nachbauer, Wolfgang; Eigentler, Andreas; Gizewski, Elke R.; Guger, Michael; Indelicato, Elisabetta; Boesch, Sylvia (Neurogenetics, 2021)
The spectrum of coenzyme Q 10 (CoQ 10 ) deficiency syndromes comprises a variety of disorders, including a form of autosomal recessive cerebellar ataxia (ARCA2) caused by mutations in the AarF domain–containing kinase 3 gene ( ADCK3 ). Due to the potential response to CoQ 10 supplementation, a timely diagnosis is crucial. Herein, we describe two siblings with a novel homozygous ADCK3 variant and an unusual presentation consisting of isolated writer’s cramp with adult-onset. Cerebellar ataxia developed later in the disease course and remained stable during the follow-up. This report highlights that ARCA2 should be considered in the differential diagnosis of familial writer’s cramp.